IMPLEMENTATION OF DIFFERENTIATED LEARNING IN ISLAMIC STUDIES AND ETHICS IN SECONDARY SCHOOLS - S Sukardi; Nurul Latifatul Inayati (Profetika: Jurnal Studi Islam, 2023)
The challenges of today's world of student learning are increasingly dynamic, this is characterized by different student interest tendencies and characters. The government, through the Ministry of Education, is aggressively discussing the concept of an independent curriculum through differentiated learning which is considered appropriate for achieving learning goals. This research aims to find out how the implementation of differentiated learning is applied to PAI subjects at Muhammadiyah Lasem Middle School. This research is based on qualitative methods, where this method is applied by collecting data such as interviews, observations, documentation, and/or other important records. With the research results stated. Firstly, teacher Pai carried out student profile mapping, secondly, the teacher carried out differentiated learning strategies, and thirdly, evaluated learning outcomes. One of the successes of differentiated learning is also supported by good cooperation between the class teacher and student parents in equalizing perceptions.